2015
DOI: 10.1016/j.scr.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting actin depolymerization enhances osteoblast differentiation and bone formation in human stromal stem cells

Abstract: Remodeling of the actin cytoskeleton through actin dynamics is involved in a number of biological processes, but its role in human stromal (skeletal) stem cells (hMSCs) differentiation is poorly understood. In the present study, we demonstrated that stabilizing actin filaments by inhibiting gene expression of the two main actin depolymerizing factors (ADFs): Cofilin 1 (CFL1) and Destrin (DSTN) in hMSCs, enhanced cell viability and differentiation into osteoblastic cells (OB) in vitro, as well as heterotopic bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…It has been reported that significant changes took place in the cytoskeleton during lineage commitment and differentiation of hMSC. 33, 34 During hMSCs' lineage commitment, the cells undergo significant modifications in morphology and actin cytoskeletal organization, and this participates in cell-fate determination. 33 In addition, during osteoblast differentiation, hMSCs morphologically change from fibroblast-like cells to cuboidal morphology, which is associated with changes in the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that significant changes took place in the cytoskeleton during lineage commitment and differentiation of hMSC. 33, 34 During hMSCs' lineage commitment, the cells undergo significant modifications in morphology and actin cytoskeletal organization, and this participates in cell-fate determination. 33 In addition, during osteoblast differentiation, hMSCs morphologically change from fibroblast-like cells to cuboidal morphology, which is associated with changes in the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…33, 34 During hMSCs' lineage commitment, the cells undergo significant modifications in morphology and actin cytoskeletal organization, and this participates in cell-fate determination. 33 In addition, during osteoblast differentiation, hMSCs morphologically change from fibroblast-like cells to cuboidal morphology, which is associated with changes in the cytoskeleton. 35 Similarly, during differentiation of hMSCs to adipocytes, significant changes in cell morphology takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of cellular shape and functional outcome may be explained by changes in actin dynamics. We have previously demonstrated that changes in cell shape induced by alternations in the actin cytoskeleton structure determine differentiation outcome of hBM‐MSCs with cellular changes associated with actin de‐polymerization led to enhanced adipocytic differentiation, whereas inhibition of actin de‐polymerization increased osteoblast formation of hBM‐MSCs . Furthermore, one study also shows that stimulation of a immunomodulating pathway can lead to a morphological response in BM‐MSCs .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cell morphology and biological functions have been studied in respect to changes in cytoskeletal fibers (actin and tubulin) that mediate cellular adaptation to microenvironmental stimuli and facilitate intracellular signal transduction. For example, the actin cytoskeleton plays a role in hBM‐MSC lineage commitment, and microtubules are key players in cell proliferation and have been reported to contribute to osteoblast differentiation . Alterations in cell shape affects actin stress fibers, which through intracellular signaling pathways initiate cell lineage commitment .…”
Section: Introductionmentioning
confidence: 99%